AGRONOMIC PERFORMANCE OF SUPERIOR SOYBEAN CULTIVERS IN INTERCROPPING WITH MAIZE USING LIQUID ORGANIC FERTILIZER BASED ON AZOLLA PINNATA - Rahma Harti, Adi Oksifa; Sukmawati, Dety; Indriana , Kovertina Rakhmi; Marina, Ida; Komariah, Ai (Journal of Innovation and Research in Agriculture, 2025)
Soybean is lots of plants contain beneficial nutrition for Indonesian society. The need for soybeans continues to increase every year while national soybean production is still low. One of the efforts to increase soybean production is by intercropping with corn. Competition in obtaining growth factors, one of which is nutrients, is a major problem in intercropping, therefore it is necessary to add environmentally friendly nutrients such as Azolla pinnata. This study aims to analyze the performance of soybean cultivars planted by intercropping with corn by administering LOF Azolla pinnata. The research method used a randomized block design (RBD) which consisted of 24 treatment combinations and was repeated twice to see the effectiveness of the treatment, analyzed with response surface regression. The results of the research show Cultivars Anjasmoro, Dega 1 and Gepak Kuning show most agronomic appearance good with administration of LOF Azolla dose 400 ml.L -1. results study this show giving LOF to cultivation plant in a manner intercropping could conducted for minimize impact negative competition between plant on system intercropping. Selection could conducted with see correlation between character which have correlation most tightly with character result.